Melanin-like nanoparticles loaded with an angiotensin antagonist for an improved photothermal cancer therapy. (23rd January 2020) - Zhou, Zhengjie; Yan, Yang; Zhang, Qiang; Cheng, Yiyun
Abstract : Losartan decompresses tumor blood vessels and degrades extracellular matrix in tumor to enhance nanoparticle penetration and accumulation in tumors, resulting in improved photothermal killing of tumor cells. Abstract : An abnormal tumor growth induces solid stress in tumors, thus reducing blood perfusion. As a result, the impaired blood perfusion, with dense interstitial matrix in tumors significantly reduces the penetration and efficacy of nanotherapeutics. In this study, we have developed a losartan-loaded polydopamine nanoparticle (PLST) for the enhanced delivery of nanoparticles to tumors and improved photothermal cancer therapy. Losartan, an angiotensin inhibitor, is also able to alleviate the solid stress in tumors. It was laden on polydopamine nanoparticles via π–π stacking and was released upon tumor extracellular acidity. PLST reduced collagen production in vitro along with the lowered expression of profibrotic factors of TGF-β1, CCN2, and TIMP-1. The in vivo studies reveal that PLST reduced solid stress in tumors, and the amount of PLST accumulated in tumors was enhanced. The efficiency of the photothermal ablation of tumors was significantly enhanced by using PLST.